Dissection Level Within Aortic Wall Layers is Associated with Propagation of Type B Aortic Dissection: A Swine Model Study. (September 2019) - Guo, Baolei; Dong, Zhihui; Pirola, Selene; Liu, Yifan; Menichini, Claudia; Xu, Xiao Yun; Guo, Daqiao; Fu, Weiguo
Abstract : Objective: Haemodynamic and geometric factors play pivotal roles in the propagation of acute type B aortic dissection (TBAD). The aim of this study was to evaluate the association between dissection level within all aortic layers and the propagation of acute TBAD in porcine aorta. Methods: In twelve pigs, two models of TBAD were created. In model A (n = 6), the aortic wall tear was superficial and close to the intima (thin intimal flap), whereas in model B (n = 6) it was deep and close to the adventitia (thick intimal flap). Dissection propagation was evaluated using angiography or computed tomography scans, and the haemodynamic measurements were acquired using Doppler wires. Most pigs were followed up at 1, 3, 6, 12, 18, and up to 24 months; four animals were euthanised at three and six months, respectively (two from each group). Results: Both models were successfully created. No statistical difference was observed for the median antegrade propagation distance intra-operatively between the two models ( p = .092). At 24 months, the longitudinal propagation distance was significantly greater in model B than in model A ( p = .016). No statistical difference in retrograde propagation was noted ( p = .691). Over time, aortic wall dissection progressed most notably over the first three months in model A, whereas it continued over the first 12 months in model B. Flow velocity was significantly greater in the true lumen than in false lumen at the level of the primary tear ( p = .001) and in the middle of the dissection ( p = .004). The histopathological images at three and six months demonstrated the fibres were stretched linearly at the outside wall of false lumen in both models, while the depth of intimal tears developed to be superficial and similar at the distal dissection. Conclusion: In this swine model of TBAD, a deeper intimal tear resulted in greater dissection propagation.